A joint allergist/cardiologist classification for thienopyridines hypersensitivity reactions based on their symptomatic patterns and its impact on the management strategies. (1st November 2016) - Calogiuri, G.F.; Al-Sowaidi, S.; Nettis, E.; Cortellini, G.; Macchia, L.; Vacca, A.; Kounis, N.G.
Abstract: The role and importance of thienopyridines such as ticlopidine, clopidogrel, and prasugrel is well-established for several indications, ranging from prevention of acute coronary syndromes to percutaneous coronary interventions, where the dual antiplatelet therapy represents the gold standard to avoid de novo coronary stenosis. However, there is a significant cohort of patients with coronary artery disease who may manifest hypersensitivity reactions to thienopyridines. The examination of the various case reports from medical literature leads to identify mainly four clinical patterns of hypersensitivity to thienopyridines which involves more frequently cutaneous, hematologic, and articular tissues, therefore the kind and predominance of clinical symptoms may determine a different clinical approach to overcome or neutralize thienopyridines hypersensitivity.